The Influence of Lifestyle and Brand Image on Purchasing Decisions for Coca-Cola Products in Surabaya - Anggraeni, Aulia Dwi; Wardhani, Nuruni Ika Kusuma (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
This research aims to analyze the influence of lifestyle and brand image on purchasing decisions for Coca-Cola products in Surabaya. This research uses quantitative methods with the sampling technique used, namely Non Probability Sampling, a method of sampling that does not offer every component or member of the population an equal chance to be chosen as a sample using a purposeful sampling methodology. The research sample consisted of 80 respondents who were consumers aged over 17 years who specifically purchased and consumed Coca-Cola products in Surabaya. The technique for collecting data uses primary data obtained through questionnaires distributed to respondents. The analysis method employed in this study uses the PLS or Partial Least Square application and uses validity testing, reliability testing and hypothesis testing. Based on the research results, we can concluded that lifestyle has a positive and significant effect on purchase decisions, acceptable, with a path coefficient of 0.518627, and a T-statistic value of 5.126284. Likewise, the brand image variable has a positive and significant effect on purchasing decisions, acceptable, with path coefficients of 0.372649, and a T-statistic value of 3.926683 for Coca-Cola products in Surabaya.